Implementation Of Problem-Based Learning Using Animation In Akidah Akhlak Instruction: A Case Study At Mi Bahrul Ulum Majalaya - Wahyudin, Wahyudin; Darmiyanti, Astuti; Ferianto, Ferianto (IJGIE (International Journal of Graduate of Islamic Education), 2026)
This study aims to examine the implementation of Problem-Based Learning (PBL) supported by animated media in Aqidah Akhlak instruction at MI Bahrul Ulum Majalaya. This study employs a qualitative approach with a case study design to gain an in-depth understanding of the learning process, teacher strategies, and student responses to the implementation of PBL integrated with animated media. Data collection was conducted through observation, interviews, and documentation, followed by thematic analysis. The results indicate that the implementation of PBL supported by animated media enhances student engagement and understanding of Akidah Akhlak material. Students actively participate in identifying problems, discussing solutions, and presenting group work outcomes, thereby strengthening their critical thinking, collaboration, and communication skills. Observation data showed that approximately 90% of students demonstrated attention and active participation during the learning process. Additionally, the learning process became more interactive and contextual, thereby fostering increased student motivation. The novelty of this study lies in the integration of PBL with animation media in Akidah Akhlak instruction within the context of elementary madrasahs through a qualitative case study approach, a topic that has rarely been explored in depth. Although there were constraints in the form of limited teacher technological competence and digital facilities, these did not significantly hinder the effectiveness of learning. Overall, the findings of this study indicate that PBL supported by animated media is an effective approach in improving the quality of learning, although it still requires support in the form of technological and facility enhancements. This study provides theoretical and practical contributions to the development of innovative learning strategies in elementary education, particularly in Akidah Akhlak instruction